Additive manufacturing of pure Ti with superior mechanical performance, low cost, and biocompatibility for potential replacement of Ti-6Al-4V. (November 2020) - Dong, Y.P.; Tang, J.C.; Wang, D.W.; Wang, N.; He, Z.D.; Li, J.; Zhao, D.P.; Yan, M.
Abstract: Although numerous reports have elucidated the neurotoxic impacts of Ti-6Al-4V (Ti64) due to the presence of vanadium, it is the most widely used biomedical Ti material. This is because it exhibits significantly better mechanical performance characteristics than those of pure Ti. In addition to the possibility of facilitating the production of customized medicines, selective laser melting (SLM) additive manufacturing (AM) can enable pure Ti to match the properties of Ti64 by utilizing several mechanisms such as grain refinement and solid solution strengthening. These results can be obtained due to the high cooling rate of the AM process and via a possible modification in the alloy chemistry of Ti. Herein, we report a novel approach that endows the pure Ti prepared via AM with excellent mechanical properties (ultimate tensile strength, yield strength, elongation, and microhardness of 1057.05 MPa, 784.59 MPa, 24.09%, and 307 Hv, respectively), corrosion resistance, and biocompatibility, while significantly reducing the cost of the powder. The pure Ti material developed in this study has significant potential for use as an advanced biomedical material in a variety of applications such as dental and bone structure replacement. Furthermore, it can act as a low-cost alternative to biomedical materials such as Ti-6Al-4V. Graphical abstract: Unlabelled Image Highlights: Additively manufactured pure Ti exhibits excellent strength, low toxicity and high cost affordability, by a designed strength-ductility tradeoff. As-printed HDH-Ti displays high ultimate tensile strength and yield strength, as well as good elongation. In vitro biocompatibility test shows the as-printed HDH-Ti having better biocompatibility than the as-printed atomized Ti samples. The obtained Ti materials have great potential for replacing Ti-6Al-4V in biomedical applications.